Why Kant’s “Ethical State” Might Prove Instrumental in Challenging Current Social Pathologies - Herta Nagl-Docekal (Кантовский сборник, 2021)
As recent social research demonstrates, the life world is increasingly impacted by a corrosion of social bonds and aggressive habits expressed, for instance, in hate speech in the social media. Significantly, such phenomena have not been prevented from evolving within the framework of constitutional liberal states. In search of an appropriate mode of challenging the current social pathologies, we should examine Kant’s claim that, alongside the “juridico-civil (political) state”, an “ethico-civil state”, uniting human beings “under laws of virtue alone”, needs to be established and cultivated. Kant’s claim is discussed in comparison with “postmetaphysical” conceptions of morality, as maintained by Rawls and Habermas. These prove deficient owing to their contract-based approach. Important in the examination of the key idea of the “state of virtue” is Kant’s thesis that such a state “cannot be realized (by human organization) except in the form of a church”. In view of the fact that, today, in many parts of the world significant segments of the population adhere to agnostic or atheistic convictions, the focus is placed on Kant’s specific conception of “church” that is clearly distinct from “historical” creeds and religious practices, and on the way in which he addresses non-believers, since he insists on the intrinsic relation between morality and the “purely moral religion”. Based on these reflections, the relevance of Kant’s argument that it is “a duty of the entire human race” to establish a community in which people mutually support one another in the cultivation of moral sensitivity is scrutinised.